Effects of Different Levels of Garlic Straw Powder on Growth Performance, Meat Quality, Antioxidant and Intestinal Mucosal Morphology of Yellow-Feathered Broilers - Liao, Shuang; Liao, Liping; Huang, Peng; Wang, Yanzhou; Zhu, Siyuan; Wang, Xin; Lv, Tuo; Li, Yinghui; Fan, Zhiyong; Liu, Touming; Lin, Qian (Frontiers in Physiology, 2022)
The purpose of this study was to investigate the effects of garlic straw powder (0%, 3%, 6%, 9%) included in diets on production performance, meat quality, antioxidant capacity, and intestinal mucosal morphology of yellow-feathered broilers. A total of 360 yellow-feathered broilers were randomly divided into one of four diets and fed for 28 days.The results showed that: Growth performance: Compared with control group, there were no significant differences in average initial weight, average final weight, ADG, ADFI and FCR among experimental groups (P > 0.05); Breast muscle quality: Compared with the control group, drip loss was significantly decreased in all experimental groups (P <0.05), but there were no significant differences in shear force, meat color, cooking loss and PH value (P > 0.05). Compared with the control group, breast muscle color in experimental group showed an upward trend (0.05 0.05); Serum antioxidant indexes: Compared with the control group, GSH-Px was increased by 11.44%, 6.73% and 21.38% when the garlic straw powder supplemental level was 3%, 6% and 9%, respectively (P <0.05). Compared with the control group, SOD increased by 21.85% when the garlic straw powder content was 3% (P < 0.05). In addition, there were no significant differences in CAT, GSH and T-AOC compared with the control group (P >0.05); Intestinal mucosal morphology: Compared with the control group, there were no significant differences in villus height, crypt depth, villus height/crypt depth and intestinal wall thickness in duodenum, jejunum and ileum of experimental groups (P > 0.05). In conclusion, diets supplemented with different levels of garlic straw powder can improve meat quality and antioxidant performance of broilers and have no negative effects on growth performance and intestinal development of broilers. Among them, the optimal supplemental level of garlic straw powder for broilers is 6mg/kg.